How research can support efforts to control avian flu in developing countries: first steps towards a research action plan - International Livestock Research Institute; International Food Policy Research Institute (International Livestock Research Institute, 2006)
Report of an international consultation — The Research Community’s Response to Avian Influenza, with Special Reference to the Needs of Developing Countries, held 14-16 June 2006 in Nairobi, Kenya — organised by the International Food Policy Research Institute (IFPRI) and the International Livestock Research Institute (ILRI).